Perbandingan Usability Learning Management System Edmodo dan Google Classroom Menggunakan Metode Cognitive Walkthrough dan User Experience Questionnaire (UEQ) (Studi Kasus: SMKN 3 Malang) - Syattya Permata Anugrah; Retno Indah Rokhmawati; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The implementation of Learning Management System (LMS) at SMKN 3 Malang there are still problems encountered by students due to their low literacy power, appearance that is difficult to understand and users do not understand some features in the system. So that problems arise in the usability and learnability aspects of the LMS. Researchers compared usability on the two LMS used, which are Edmodo and Google Classroom, using the Cognitive Walkthrough method for testing usability and User Experience Questionnaire (UEQ) to get the user experience of students against the Google Classroom and Edmodo LMS. Respondents involved five students for the Cognitive Walkthrough test and 30 students for the User Experience Questionnaire (UEQ) method. Cognitive Walkthrough test results show the Google Classroom LMS has a total of eight problems, then on LMS Edmodo there are nine problems. On the results of the distribution of the UEQ questionnaire, Edmodo excelled in aspects perspicuity, dependability, stimulation, and novelty. While Google Classroom excels in aspects of attractiveness and efficiency. From these results, Google Classroom is more recommended for new users because it excels in the learnability aspect, but in terms of user experience, Edmodo is more recommended for use by students of SMKN 3 Malang in teaching and learning activities in class.